The burden of neutropenic sepsis in patients with advanced non-small cell lung cancer treated with single-agent docetaxel: A retrospective study. (November 2017) - Talbot, Toby; Dangoor, Adam; Shah, Riyaz; Naik, Jay; Talbot, Denis; Lester, Jason F.; Cipelli, Riccardo; Hodgson, Matt; Patel, Ajay; Summerhayes, Max; Newsom-Davis, Thomas
Highlights: 17.4% of patients experienced ≥1 episode of confirmed/suspected neutropenic sepsis. The mean cost of treatment and hospitalisation for confirmed NS was £3163/patient. The mean cost of treatment and hospitalisation for suspected NS was £1790/patient. Mean LOS for unplanned admissions for confirmed or suspected NS was 9.2 and 4.7 days, respectively. The burden of NS on patients and hospital resources were previously underestimated. Abstract: Objectives: To describe rates of confirmed and suspected neutropenic sepsis (NS) and associated hospital resource utilisation in patients with non-small cell lung cancer (NSCLC) treated with docetaxel monotherapy following relapse after ≥1 line of chemotherapy in routine UK clinical practice. Materials and methods: A multi-centre, retrospective, observational research study was conducted in seven centres across England and Wales. Adult patients with stage III/IV NSCLC initiated on docetaxel monotherapy between 2010 and 2016 in routine clinical practice (aged ≥18 years at initiation) following failure of first-line chemotherapy were eligible. Data were collected from hospital medical records between May 2016 and July 2016, on all episodes of confirmed or suspected NS related to docetaxel monotherapy, including patient characteristics. Episodes of confirmed NS were defined as documented absolute neutrophil count <1.0 × 10 9 /L, plus temperature >38 °C or other signs/symptoms of sepsis, otherwise episodes were classified as suspected NS. Results: 121 patients were included (median age 65.5 years; 57.9% male; median 4.0 cycles of docetaxel; 19.8% treated with prophylactic granulocyte-colony stimulating factor). Episodes of confirmed or suspected NS were recorded in 21/121 (17.4%) patients (11 confirmed episodes in 11 [9.1%] patients and 11 suspected episodes in 10 [8.3%] patients). Resource utilisation data were available for 21/22 episodes; the mean length of stay for confirmed NS admissions (n = 11) was 9.2 (SD: 9.2) days and for suspected NS admissions (n = 10) was 4.7 (SD: 4.6) days. The most commonly prescribed treatment for NS was piperacillin/tazobactam therapy (46.5% of all documented treatments). The mean total costs of managing patients with confirmed NS (n = 11) and suspected NS (n = 9) were £3163 (SD: £2921) and £1790 (SD: £1585) per patient, respectively. Conclusion: Rates of confirmed NS in UK clinical practice were broadly similar to those reported in clinical trials; however, the burden of suspected NS, not routinely reported elsewhere, is also substantial.